2019
DOI: 10.3389/fimmu.2019.01156
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki Disease: The Role of Immune Complexes Revisited

Abstract: Kawasaki disease (KD) is an inflammatory disease in children associated with vasculitis affecting predominantly the coronary arteries and is now the most common cause of acquired heart disease in children in developed countries. The etiology of KD is unknown but epidemiological studies implicate an infectious agent or toxin, which causes disease in genetically predisposed individuals. The presence of immune complexes (ICs) in the serum of children with KD was established in numerous studies during the 1970s an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 107 publications
(132 reference statements)
4
80
1
1
Order By: Relevance
“…The positive correlation between KD and infectious diseases are likely help to recognize the role of superantigens involving the heart and blood vessels(2,3) Sinusitis con rmed in 26 studied children regardless of KD, is very close to Sherman et and Slavin et al studies, they found community acquired sinusitis as one of the most common infections for medical attention and visited by pediatrician (10,11,13,14 ) like previous studies, this study determined the probable role for infectious etiologies in pediatric group (eg: otitis media with effusion; sinusitis ,pneumonia, septic arthritis, and other diseases ) [7][8][9] Shermin et al de ned sinusitis was a common upper respiratory infections in pediatric diseases (11) In deed ,Lloyd et al showed KD caused by an infectious agent (10). Hypothesis of super antigens is one of the most important explanations for many diseases including rhino sinusitis and KD (7)(8)(9)(10). Obstruction of the external meatus of para nasal sinuses and eustachian tube due to in ammation, hypertrophic mucosa, accumulation of secretions in the respiratory tract and metaplastic changes can lead to more severe and longer infection (16,17 ).…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…The positive correlation between KD and infectious diseases are likely help to recognize the role of superantigens involving the heart and blood vessels(2,3) Sinusitis con rmed in 26 studied children regardless of KD, is very close to Sherman et and Slavin et al studies, they found community acquired sinusitis as one of the most common infections for medical attention and visited by pediatrician (10,11,13,14 ) like previous studies, this study determined the probable role for infectious etiologies in pediatric group (eg: otitis media with effusion; sinusitis ,pneumonia, septic arthritis, and other diseases ) [7][8][9] Shermin et al de ned sinusitis was a common upper respiratory infections in pediatric diseases (11) In deed ,Lloyd et al showed KD caused by an infectious agent (10). Hypothesis of super antigens is one of the most important explanations for many diseases including rhino sinusitis and KD (7)(8)(9)(10). Obstruction of the external meatus of para nasal sinuses and eustachian tube due to in ammation, hypertrophic mucosa, accumulation of secretions in the respiratory tract and metaplastic changes can lead to more severe and longer infection (16,17 ).…”
Section: Methodssupporting
confidence: 85%
“…According to the American Heart Association (AHA) criteria fever lasting more than 5 days is essential for KD diagnosis with two or three principal clinical features of KD) without a known infection source. (6) The super antigen hypothesis; immune response, and genetic background on the response to infectious stimuli discussed by some authors (7)(8)(9). Nagata reported causes of KD in pediatrics (7) Nakamura et al studied etiological signi cance of infectious stimuli in KD (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It comes with no surprise that elevated IL-1b and IL-6 levels in addition to a monotype profile shifted to intermediate monocytes are common hallmarks in KD. 24 MAS is a complication in about 2% of patients with KD; however, the incidence is likely underestimated as many clinical and laboratory features of both diseases overlap and the HLH 2009 criteria have low sensitivity and specificity for the diagnosis of MAS complicating KD. 25 Recently, classification criteria for MAS in the paediatric population have been released and will allow to provide more reliable epidemiological data.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, a link between coronaviruses and Kawasaki syndrome was first proposed in 2005 ( 23 ). However, a causal relation has thus far not been proven, and the cause of Kawasaki Disease is currently unknown ( 24 , 25 ). Awareness of the new hyperinflammatory condition affecting children was raised by clinicians in the UK, leading to an alert by the UK National Health Service, on April 25th 2020.…”
Section: Statementmentioning
confidence: 99%